Ministers - Chapple, A. H. (Great Britain, 1968)
The book contents some articles such as: What is a Christian?, Where is Thy God?, The cross beyond the gate$1! = (Bto help the readers to understand more about being a Christian in the world.s
Keywords: Sermons, English